Legalitas Pengalihan Fungsi Pinggir Kanal Banjir Krueng Aceh Menurut Konsep Milk Al-Daulah (Studi Pembangunan Gedung ANRI dan Rumah Susun ASN PUPR di Bakoy, Aceh Besar) - Nasywa, Rizkia; Fadhilah (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2026)
This research aims to analyze the legality of land use conversion along the Krueng Aceh Flood Canal for the construction of the National Archives of the Republic of Indonesia (ANRI) Building and the Flats for Civil Servants of the Ministry of Public Works and Housing (PUPR), from the perspective of positive law and the Islamic law concept of milk al-daulah. This research adopts an empirical juridical approach with a qualitative method. Primary data were obtained through interviews with the Sumatra I River Basin Authority and the Aceh Besar Public Works and Housing Office, while secondary data were collected from regulatory documents, site maps, and scholarly literature. The findings indicate that both projects comply with legal and administrative requirements, supported by the 2014 Minister of Finance approval, the 2019 Building Permit (IMB), and the 2024 Building Approval (PBG). Field verification confirmed the sites are outside the river border. However, regulatory differences exist between Qanun Aceh Besar No. 4/2013 and PUPR Regulation No. 28/2015. The latter applies in practice due to the canal’s technical nature. In Islamic law, the land is classified as milk al-daulah, making its use lawful for public benefit.